MHD mixed convection peristaltic flow with variable viscosity and thermal conductivity - Hayat, T.; Abbasi, F.M.; Ahmad, B.; Alsaedi, A. (Universiti Kebangsaan Malaysia, 2014)
This article concerns with a mixed convection peristaltic flow of an electrically conducting fluid in an inclined asymmetric channel. Analysis has been carried out in the presence of Joule heating. The fluid viscosity and thermal conductivity are assumed to vary as a linear function of temperature. A nonlinear coupled governing system is computed. Numerical results were presented for the velocity, pressure gradient, temperature and streamlines. Heat transfer rate at the wall is computed and analyzed. Graphs reflecting the contributions of embedded parameters were discussed.